PTU-056 Highly Successful, Minimally Invasive Enteral Access By Double-balloon Enteroscopy (dbe) And Laparoscopic-assisted Dbe. (9th June 2014) - Shepherd, TC; Epstein, O; Khan, A; Pring, ET; Varcada, M; Rahman, S; Despott, EJ
Abstract : Introduction: Patients with chronic gastroparesis frequently require prolonged enteral feeding via the jejunal route. This is often achieved through the placement of a percutaneous endoscopic gastrostomy with jejunal extension (PEG-J) or a surgically placed jejunostomy (SJ). Direct percutaneous endoscopic jejunostomy (DPEJ) is increasingly used as an alternative to these modalities: Avoiding the intrinsic problems associated with the narrow calibre PEG-J and the tendency of displacement and retrograde migration; and is less invasive than SJ insertion, which also requires an enterotomy and enteropexy. Although progress with deep enteroscopy over the last decade has facilitated DPEJ placement, the presence of post-surgical intra-abdominal adhesive disease may still reduce success rates and procedure safety. In this setting, miniport laparoscopic-assisted DBE (lap-DBE) has the potential to provide safe and successful placement while maintaining the relatively minimally invasive approach of the endoscopic pull-through technique. Methods: Prospective assessment of outcomes of DPEJ placement by DBE and lap-DBE placed at our tertiary referral institution since June 2012. Results: 10 patients (6 [60%] female, median age 40 years [range: 27–43 years]) with chronic gastroparesis underwent DBE or lap-DBE facilitated DPEJ placement. Miniport laparoscopic assistance was only required in patients with a history of abdominal surgery (30% [3/10]) and allowed us to identify and divide any underlying adhesions laparoscopically, facilitating DPEJ placement under direct endoscopic and laparoscopic vision, without the need for an enterotomy or surgical enteropexy. In this series DPEJ placement was successful in all 10 patients: Estimated depth of insertion [mean±SD] 66 ± 12 centimetres post-pylorus and procedure time [mean±SD] 49 ± 114 min. There were no immediate procedure-related complications and no delayed complications, morbidity or mortality at a mean follow-up of 339 days [range: 175–576 days]. Conclusion: DPEJ placement by DBE is successful and safe. In patients with a history of abdominal surgery and underlying adhesive disease, lap-DBE should be considered, as it may enhance procedure success and safety. Disclosure of Interest: None Declared.